Pembelajaran Matematika Budaya (Etnomatematika) Berbantuan Aplikasi Math City Map untuk Meningkatkan Kemampuan Berpikir Kritis Peserta Didik - Iqbal Ma'ruf Al Ashari; Desi Andryani Lubis; Ludi Arianto; Amidi (JEID: Journal of Educational Integration and Development, 2021)
Mathematics is a compulsory subject that is taught from elementary school (SD) to university level. Although it is a compulsory subject, students complain about mathematics as an unpleasant subject. This study aims to provide an easier understanding of mathematics to students, especially the relationship between mathematics and culture (ethnomathematics) by using the Math City Map application. The research method used in this study is a literature study by comparing previous research journals that underlie the research. The output of the research is in the form of learning cultural mathematics (ethnomathematics) which is more fun by utilizing the Math City Map application that is used by students via cell phone media. Where students will be invited to use the application to explore and study local culture associated with the mathematical aspect so that the mathematical critical thinking skills possessed by students will increase.